2020
DOI: 10.1002/ece3.6622
|View full text |Cite
|
Sign up to set email alerts
|

Insectivorous birds can see and smell systemically herbivore‐induced pines

Abstract: Several studies have shown that insectivorous birds are attracted to herbivore‐damaged trees even when they cannot see or smell the actual herbivores or their feces. However, it often remained an open question whether birds are attracted by herbivore‐induced changes in leaf odor or in leaf light reflectance or by both types of changes. Our study addressed this question by investigating the response of great tits (Parus major) and blue tits (Cyanistes caeruleus) to Scots pine (Pinus sylvestris) damaged by pine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 90 publications
0
27
3
Order By: Relevance
“…Birds have also been shown to be attracted to trees infested by herbivores, without seeing the insects or physical foliage damage (Mäntylä et al., 2004 , 2008 , 2016 , 2020 ). Yet, only recently we started to disentangle the mechanism underlying the use of olfactory signals by birds searching for prey (Amo et al., 2013 ; Koski et al., 2015 ; but see Koski et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Birds have also been shown to be attracted to trees infested by herbivores, without seeing the insects or physical foliage damage (Mäntylä et al., 2004 , 2008 , 2016 , 2020 ). Yet, only recently we started to disentangle the mechanism underlying the use of olfactory signals by birds searching for prey (Amo et al., 2013 ; Koski et al., 2015 ; but see Koski et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amo and collaborators [40] isolated the visual and chemical cues of larvae-infested apple trees and found that great tits were attracted to infested trees when they could only smell but not when they could only see the trees. Therefore, it seems that HIPVs can attract insectivorous birds [40,42], although a previous study using artificial mixtures of volatiles has not found such an attraction [61]. The positive correlation found between avian the predation rates of artificial larvae and the quantity of emission of volatiles emitted by trees experimentally infested with caterpillars in natural conditions also suggests that olfaction may be the mechanism underlying bird attraction to caterpillar-infested trees [53], although vision may also play an important role in finding prey [42,52,57].…”
Section: Introductionmentioning
confidence: 92%
“…Previous evidence also suggests that birds use olfaction in the process of foraging. The use of olfaction during foraging seems to be an ancient trait in birds (e.g., Kiwis (Apteryx australis) [33]; Cathartes vultures [34]), where it is maintained in modern lineages (Procellariiforms [35]); penguins [36,37]; domestic chickens (Gallus gallus) [38]; and passeriformes, such as zebra finches (Taeniopygia guttata) [39], great tits (Parus major), and blue tits (Cyanistes caeruleus) [40][41][42]). The results of a recent comparative study suggest that the olfactory bulb size, a proxy of olfactory capability, varies substantially across bird species in relation to diet type and ecological conditions [43], suggesting that foraging mode has played an important role in the evolution of chemosensory abilities in birds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations